Price-level versus inflation targeting with financial market imperfections - Francisco Covas; Yahong Zhang (Bank of Canada, 2008)
This paper compares price-level-path targeting (PT) with inflation targeting (IT) in a sticky-price, dynamic, general equilibrium model augmented with imperfections in both the debt and equity markets. Using a Bayesian approach, we estimate this model for the Canadian economy. We show that the model with both debt and equity market imperfections fits the data better and use it to compare PT versus the estimated current IT regime. We find that in general PT outperforms the current IT regime. However, the gain is lower when financial market imperfections are taken into account.
Keywords: E40; E50; 330; Monetary policy framework; Inflation targets; Economic models; Finanzmarkt; Unvollkommener Markt; Preisniveau; Inflation Targeting; Preisrigidität; Gesamtwirtschaftliche Produktion; Theorie; Kanada